In Vitro Inhibition of Leishmania Attachment to Sandfly Midguts and LL-5 Cells by Divalent Metal Chelators, Anti-gp63 and Phosphoglycans - Soares, Rodrigo Pedro; Altoé, Ellen Cristina Félix; Ennes-Vidal, Vítor; da Costa, Simone M; Rangel, Elizabeth Ferreira; de Souza, Nataly Araújo; da Silva, Vanderlei Campos; Volf, Petr; d'Avila-Levy, Claudia Masini (Protist, 2017)
Leishmania braziliensis and Leishmania infantum are the causative agents of cutaneous and visceral leishmaniasis, respectively. Several aspects of the vector-parasite interaction involving gp63 and phosphoglycans have been individually assayed in different studies. However, their role under the same experimental conditions was not studied yet. Here, the roles of divalent metal chelators, anti-gp63 antibodies and purified type I phosphoglycans (PGs) were evaluated during in vitro parasite attachment to the midgut of the vector. Parasites were treated with divalent metal chelators or anti-gp63 antibodies prior to the interaction with Lutzomyia longipalpis/Lutzomyia intermedia midguts or sand fly LL-5 cells. In vitro binding system was used to examine the role of PG and gp63 in parallel. Treatment with divalent metal chelators reduced Le. infantum adhesion to the Lu. longipalpis midguts. The most effective compound (Phen) inhibited the binding in both vectors. Similar results were observed in the interaction between both Leishmania species and the cell line LL-5. Finally, parallel experiments using anti-gp63-treated parasites and PG-incubated midguts demonstrated that both approaches substantially inhibited attachment in the natural parasite-vector pairs Le. infantum/Lu. longipalpis and Le. braziliensis/Lu. intermedia. Our results suggest that gp63 and/or PG are involved in parasite attachment to the midgut of these important vectors.
Keywords: chelátory; metaloendopeptidasy; phosphoglycans; Metalloendopeptidases; Leishmania infantum; Chelating Agents; interaction.; Animals; Polysaccharides; Leishmania braziliensis; polysacharidy; Psychodidae; major surface peptidase (MSP); kovy; Metals; zvířata; gp63